2019
DOI: 10.1136/bmjopen-2019-033404
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence among prehospital care providers in India: a cross-sectional study

Abstract: ObjectivesThe purpose of this study was twofold: (1) establish the prevalence of safety threats and workplace violence (WPV) experienced by emergency medical technicians (EMTs) in a low/middle-income country with a new prehospital care system, India and (2) understand which EMTs are at particularly high risk for these experiences.SettingEMTs from four Indian states (Gujarat, Karnataka, Tamil Nadu and Telangana) were eligible to participate during the study period from July through November 2017.MethodsCross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…This study obtained a 43.3% prevalence of WPV among healthcare workers, of which 84.6% were non-physical, and the remaining 15.4% was physical. The prevalence is lower than a study conducted in China (49.2%) [17] but higher than in India (40.8%) [18]. A Turkish study of doctors identified a very high 78.1% prevalence of WPV in the emergency department [16].…”
Section: Discussionmentioning
confidence: 59%
“…This study obtained a 43.3% prevalence of WPV among healthcare workers, of which 84.6% were non-physical, and the remaining 15.4% was physical. The prevalence is lower than a study conducted in China (49.2%) [17] but higher than in India (40.8%) [18]. A Turkish study of doctors identified a very high 78.1% prevalence of WPV in the emergency department [16].…”
Section: Discussionmentioning
confidence: 59%
“…Most of the available validated questionnaires are not easy to administer and suffer from the limitation of low psychometric properties. They are unable to capture various domains comprehensively as one single scale [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of violence, which ranged between 61.-78.1% in the studies performed, was found to be 63.7% in our study. [24][25][26][27]…”
Section: Discussionmentioning
confidence: 99%